Metabolomics uncovers a link between inositol metabolism and osteosarcoma metastasis - Ren, Ling (Oncotarget, 2017)
Cancer development and progression are characterized by complex molecular events. The acquisition of these events is primarily believed to result from alterations in gene and protein expression/function. Recent studies have also suggested the role of metabolic alterations, or “metabolic reprogramming,” that may similarly contribute to these events. Indeed, our previous investigations in osteosarcoma (OS) identified metabolic changes uniquely linked to metastasis. Based on those findings, here we sought to build a more detailed understanding of the specific alterations in metabolites or metabolic pathways that may be responsible for the observed metastasis-associated metabolic alterations, suggested by gene expression data. This was pursued using a combination of high-throughput liquid- and gas-chromatography-based mass spectrometry (LC/MS and GC/MS) for a global metabolic profiling/subtraction of four pairs of high/low metastatic OS cell lines. By comparing the identity and level of the metabolites between high/low metastatic cells, several metabolic pathways were identified to be differentially activated, such as arginine, glutathione, inositol and fatty acid metabolic pathways. To further interrogate these results, we investigated the effects of inositol pathway dysregulation, through the exposure of metastatic OS cells to IP6 (inositol hexaphosphate). Although IP6 exposures had modest to minimal effects on cell proliferation, we observed reduced cellular glycolysis, down-regulation of PI3K/Akt signaling and suppression of OS metastatic progression. Collectively these data supported further investigation of metabolic sensitivities as anti-metastatic strategies in a clinical setting as well as investigation of altered metabolomics associated with metastatic progression.